Parasitism affects variation in a male damselfly sexual ornament. Issue 3 (4th May 2018) - Suhonen, Jukka; Ilvonen, Sini; Dunn, Derek W.; Dunn, Johanna; Härmä, Oskari; Ilvonen, Jaakko J.; Kaunisto, Kari M.; Krams, Indrikis
Abstract : Sexually selected ornaments in animals are costly, with parasitism often affecting the degree to which they are expressed. Male Calopteryx splendens damselflies exhibit melanised 'wing spots'. Those possessing large spots are favoured by females but also have an increased likelihood of being attacked by Calopteryx virgo, a common sympatric competitor. Melanin is used to produce the wing spots, but it is also used in immune defence against parasites that commonly infect damselflies. A total of 261 C. splendens males were collected from 26 Finnish and Latvian populations, of which half were found to be sympatric with C. virgo . It was found that males which originated from populations in which eugregarine parasites were present had smaller wing spots than individuals from parasite-free populations. Contrary to previous studies, the wing spots of C. splendens males in populations sympatric with C. virgo were not found to be smaller than those in allopatric populations. Parasite presence in C. splendens was found to be strongly associated with populations sympatric with C. virgo . The results suggest that the presence of C. virgo may increase rates of parasitism in C. splendens, and show that parasitism is an important additional factor to interspecific aggression in determining variation in the sizes of the wing spots of C. splendens males. These findings highlight a lack of understanding on the determinants of the expression of secondary sexual characters and the processes of how parasitism affects hosts.